The Wellington protest, 2022 : signs of franchised fascism in New Zealand : a thesis presented in fulfilment of the requirements for the degree of Master of Arts in Defence and Security Studies at Massey University, New Zealand - Fairhall, Zachary (Massey University, 2024)
This thesis critically examines various signs displayed over the course of the February/March 2022 anti-lockdown protest, which convoyed from around the country to Wellington and occupied Parliament grounds for three weeks, resulting in significant disruption to the city damage to Parliament grounds, and injuries to Police officers. I collected and collated images of these signs before analysing the signs’ language in order to better understand the form of socio-political movement this protest constitutes. I argue the signs of the Wellington Protest convey strong evidence of fascist language and sentiments, show transnational connections with other anti-government protest movements in the model of a globally connected franchise, and constitute the early stages of a fascist political movement that has potential flourish in New Zealand given the current strength of populist sentiment. However, the current evidence indicates that scholars and security professionals appear to have fundamentally misunderstood the concept and practices of fascism, and continue to underestimate the political forces revealed by the protest. Security scholars and professionals have an obligation to keep New Zealand informed of, and safe from the progenitors of political violence. By not understanding the anti-lockdown protest as part of a transnationally connected, franchise-able fascist movement, these scholars and practitioners forego important insight into the activities of relevant groups who, after the protest, establish political parties propaganda radio, and community fundraising networks.
Keywords: 440804 Defence studies; 440809 New Zealand government and politics